Serum immunoglobulin or albumin binding single-domain antibodies that enable tailored half-life extension of biologics in multiple animal species - Harmsen, Michiel M.; Ackerschott, Bart; de Smit, Hans (Frontiers in Immunology, 2024)
Single-domain antibody fragments (sdAbs) can be isolated from heavy-chain-only antibodies that occur in camelids or the heavy chain of conventional antibodies, that also occur in camelids. Therapeutic application of sdAbs is often complicated by their low serum half-life. Fusion to sdAb that bind to long-lived serum proteins albumin or IgG can prolong serum half-life of fusion partners. Such studies mostly focused on human application. For half-life prolongation in multiple animal species novel species cross-reacting sdAb are needed. We here describe the isolation from immunized llamas of sdAbs G6 and G13 that bound IgG of 9-10 species analysed, including horse, dog, cat, and swine, as well as sdAb A12 that bound horse, dog, swine and cat albumin. A12 bound albumin with 13 to 271 nM affinity dependent on the species. G13 affinity was difficult to determine by biolayer interferometry due to low and heterogeneous signals. G13 and G6 compete for the same binding domain on Fab fragments. Furthermore, they both lack the hallmark residues typical of camelid sdAbs derived from heavy-chain antibodies and had sequence characteristics typical of human sdAbs with high solubility and stability. This suggests they are derived from conventional llama antibodies. They most likely bind IgG through pairing with VL domains at the VH-VL interface rather than a paratope involving complementarity determining regions. None of the isolated sdAb interfered with FcRn binding to albumin or IgG, and thus do not prevent endosomal albumin/IgG-sdAb complex recycling. Fusions of albuminbinding sdAb A12 to several tetanus neurotoxin (TeNT) binding sdAbs prolonged the terminal serum half-life in piglets to about 4 days, comparable to authentic swine albumin. However, G13 conferred a much lower half-life of 0.84 days. Similarly, in horse, G13 prolonged half-life to only 1.2 days whereas A12 fused to two TeNT binding domains (T6T16A12) had a half-life of 21 days. The high half-life of T6T16A12, which earlier proved to be a highly potent TeNT antitoxin, further supports its therapeutic value. Furthermore, we have identified several additional sdAbs that enable tailored half-life extension of biologicals in multiple animal species.